METODE PEMBELAJARAN KOMBINASI (SELF DAN PEER ASSESSMENT) EFEKTIF MENINGKATKAN KETERAMPILAN MAHASISWA DI LABORATORIUM KLINIK - Lestari, Dilistia; Susiarno, Hadi; Sukandar, Hadyana (Universitas Tribhuwana Tunggadewi, 2020)
Midwife profession must have good competence because it has an impact in improving the quality of health service. Survey of Midwifery Diploma III Institutions. Midwife competencies that match work requirements are only 15%. To improve the competence of midwives, the laboratory learning process must be carried out properly according to standards. The combination of self and peer assessment methods is learning to get feedback, encourage students to be more active, independent, responsible, practice evaluation skills and encourage deep learning to maximize the achievement of competencies. The purpose of this study is to analyze the effect of a combination of self and peer assessmentlearning methods on D III Midwifery student competencies. This research is a quantitative study with a quasi-experimental pre-post test design. The study population was all students of D III Midwifery Semester III with a total of 75 people. Sampling uses simple random sampling technique which is divided into three groups for self assessment, peer assessment and a combination of self and peer assessmentmethods, each group totaling 25 people. The research instrument uses a checklist. The statistical test used is Kruskal_Wallis. the results showed that the combination of self and peer assessmentmethods showed more increases by 13.2% (p